A LITERATURA BRASILEIRA NO SISTEMA CULTURAL FRANCÊS: REPRESENTAÇÕES DO JORNAL LE MONDE EM 2014: THE BRAZILIAN LITERATURE IN THE FRENCH CULTURAL SYSTEM: LE MONDE’S REPRESENTATION IN 2014 - PIROLLI, Rosalia Rita Evaldt (Travessias Interativas, 2019)
RESUMO: Neste artigo iremos apresentar uma análise das matérias publicadas no jornal Le Monde, ao longo do ano de 2014, procurando identificar quais são as representações da literatura brasileira traduzida no sistema cultural francês. Além disso, procuraremos apontar se ainda persistem certas imagens estereotipadas ou exotizantes de nossa literatura dentro desse sistema cultural. PALAVRAS-CHAVE: Literatura brasileira traduzida. Recepção. Representação. ABSTRACT: In this paper we will present an analysis of the articles published in the Le Monde newspaper in 2014. We will identify the most common representations of translated Brazilian literature in the French cultural system. We will also point out if the stereotypical or exoticizing images of Brazilian literature are still strong in this cultural system. KEYWORDS: Translated Brazilian literature. French reception. Representation.